Effects of Three Types of Pollen on the Growth and Development of Honey Bee Larvae (Hymenoptera, Apidae) - Pang, Chunxiu; Dong, Kun; Guo, Yueqin; Ding, Guiling; Lu, Yuming; Guo, Zhanbao; Wu, Jie; Huang, Jiaxing (Frontiers in Ecology and Evolution, 2022)
Pollen serves as an essential protein source for honey bee larvae. The nutrients in pollen greatly influence larval growth and development. Here, survival, the prepupal weight, the developmental stage, pollen digestibility and midgut cell proliferation in honey bee (Apis mellifera L.) larvae were evaluated by in vitro larval rearing and 5-ethynyl-2´-deoxyuridine (EdU) assays for three single pollens (Brassica napus L., Armeniaca sibirica L. and Pyrus bretschneideri Rehd.) and a pollen mixture (mixture of the three pollens in equal proportions). The results showed that the survival rate of larvae fed 10 mg of rape pollen was lowest (P < 0.05), but there were no notable differences in the survival rate among the groups receiving the other types and doses of pollen (P > 0.05). The prepupal weight of larvae fed apricot pollen was significantly lower than those of the other groups (P < 0.05). The digestibility of rape pollen and the pollen mixture were dramatically higher than those of apricot and pear pollen (P < 0.05). Pear and apricot pollen had negative effects on the proliferation of the cell nuclear area in the midgut in the early larval stage (P < 0.05). Cell proliferation in the larval midgut was clearly observed. In conclusion, midgut cell proliferation detected by the EdU assay could be an effective method to assess the pollen nutritive value in honey bees. Compared to apricot and pear pollen, rape pollen was more beneficial in larval honey bee growth and development.